Profile of Superior High School Students’ Higher Order Thinking Skills on Stoichiometry Topic - Abdullah Abdullah; Rasmiwetti Rasmiwetti; Ardiansyah Ardiansyah (Universitas Riau, 2019)
The world has entered the industrial revolution (RI) 4.0 which is supported by digital technology and automation in various fields. RI 4.0 resulted in changes in the social order, specifically the need for skills in this era. The top 3 skills needed in the 21st century are complex problem solving, critical thinking, and creativity. All of these skills can be classified into Higher Order Thinking Skills (HOTS). HOTS is a thinking skill that depends on the ability to analyze, create, and evaluate all aspects and problems. This research aims to develop valid problems to measure HOTS for students on stoichiometry topic and evaluate students’ HOTS on stoichiometry topic. Research is a development research type formative research that consists of analyzing, designing, evaluating, and revising. All data are analyzed using a descriptive technique. A subject in this research is students of superior high school in Pekanbaru. The results of this research are: (1) three of valid HOTS problems on stoichiometry (2) value of students' HOTS on stoichiometry is 35.16 which put in a medium category